Towards an integrated historical biogeography of the Neotropical lowland avifauna: combining diversification analysis and landscape evolution - Ribas, Camila C. (2012)
Abstract – The importance of landscape evolution as driver of biotic diversification in the Neotropical lowlands has long been appreciated, but no clear common mechanisms have been revealed. We suggest that three main issues have collaborated to this: (i) poor understanding of earth history; (ii) problems with testing diversification hypotheses; and (iii) poor representation of diversity by current taxonomy. Thus, in order to study diversification patterns, some basic steps need to be observed: (i) the units of biodiversity need to be properly recognized through taxonomic reviews, with good geographic sampling; (ii) diversification patterns need to be carefully confronted to new information on landscape history and (iii) hypotheses need to be evaluated against direct and unambiguous predictions from alternative historical scenarios. Here we show how studies that sample all evolutionary units and use integrative approaches that combine diversification analysis with detailed data on earth history can provide new insights on the role of historical factors on the diversification of Neotropical organisms. The results presented show that both paleogeographic and paleoclimatic processes may have had an important role in the diversification of lowland Neotropical avian groups during the Pleistocene and before.